Arabic Language Module For Madrasah Ibtidaiyah - Sanjaya, Budi; Hidayat, Wahyu (Ijaz Arabi Journal of Arabic Learning, 2024)
This study aims to analyze the effectiveness of using Arabic language modules developed for students of Madrasah Ibtidaiyah.  The material represented essential learning and was relevant to everyday life. This study uses Design and Development Research (DDR) with the ADDIE model. The effectiveness testing stage was carried out at MIS of Nurul Ijtihad Lubuk Gaung, Indonesia, involving ten third-grade student participants. Qualitative data comes from the validation of media, material, language, and teacher practitioner experts. Meanwhile, quantitative data is obtained from test results. Data were analyzed qualitatively, and quantitative data were analyzed using paired t-test analysis. The study results showed that this Arabic language module was feasible and well-used for teaching Arabic in elementary schools. It also shows the development of significant student learning outcomes using this module.